Pemanfaatan Aplikasi Deteksi Birahi Sapi Perah dan Monitoring Suhu Kandang Berbasis IoT Pada UD. Dewi Sri Desa Ranuklindungan Kecamatan Grati, Kabupaten Pasuruan - Oktriza Melfazen; Oktavia Rahayu Puspitarini; Unung Lesmanah (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
The main challenges in optimising dairy farm productivity are lambing and managing barn temperature and humidity. Timely detection of lambing is key to successful reproduction. IoT-based app detects oestrus and monitors barn temperature. The system calculates the cow's fertile period and alerts the farmer for timely insemination, increasing the chances of reproductive success. IoT-connected sensors monitor barn temperature and humidity, maintaining a stable environment for the cows and increasing productivity.